2005
DOI: 10.1002/pbc.20512
|View full text |Cite
|
Sign up to set email alerts
|

Osteopenia, physical activity and health‐related quality of life in survivors of brain tumors treated in childhood

Abstract: This pilot study demonstrates that in survivors of brain tumors treated in childhood, radiation therapy is associated with significant loss of bone mineral. Among these survivors, HRQL is less, pain is more severe and ambulation is more restricted in those with low BMD scores. The reduction in HRQL is reflected in diminished physical activity. A larger multi-center study is needed to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 31 publications
2
57
0
4
Order By: Relevance
“…Only a limited number of QOL studies have been conducted with children, with much of the research focusing on the areas of pediatric oncology (Eiser, Eiser, & Stride, 2005;Odame et al, 2006;Russell, Hudson, Long, & Phipps, 2006) and debilitating chronic illnesses, such as rheumatoid arthritis (Brunner et al, 2006;Riddle et al, 2006;Sawyer et al, 2005) and cystic fibrosis (Janse, Sinnema, Uiterwaal, Kimpen, & Gemke, 2004;Koscik et al, 2005;Thomas, Mitchell, O'Rourke, & Wainwright, 2006).…”
Section: Quality Of Life and Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a limited number of QOL studies have been conducted with children, with much of the research focusing on the areas of pediatric oncology (Eiser, Eiser, & Stride, 2005;Odame et al, 2006;Russell, Hudson, Long, & Phipps, 2006) and debilitating chronic illnesses, such as rheumatoid arthritis (Brunner et al, 2006;Riddle et al, 2006;Sawyer et al, 2005) and cystic fibrosis (Janse, Sinnema, Uiterwaal, Kimpen, & Gemke, 2004;Koscik et al, 2005;Thomas, Mitchell, O'Rourke, & Wainwright, 2006).…”
Section: Quality Of Life and Childrenmentioning
confidence: 99%
“…The researchers found that the children receiving steroid treatments experienced the most improved QOL compared to the other groups, despite greater incidence of adverse side effects (Riddle et al, 2006). Another study, involving 25 children who survived brain tumors (astrocytoma or medullablastoma) compared QOL between those treat with and without radiation (Odame et al, 2006). The results showed that the survivors treated with radiation therapy had lower QOL scores and diminished physical activity (Odame et al, 2006).…”
Section: Quality Of Life and Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Poorer HRQoL has been associated with factors such as low IQ 11,12 and poor social, 9 physical, 13,14 behavioral, 11 and emotional functioning.…”
mentioning
confidence: 99%
“…However, few of these studies were confined to children with solid tumors, and their results were conflicting [20,21,22,23]. The discrepancies may be attributed in part to the small sample sizes and in part to the large number of factors that affect bone mineral density (BMD) in oncology patients including treatment toxicity (irradiation [4,6,7,9,10,21,22], chemotherapy agents with direct (methotrexate [24,25]) or indirect (ifosfamide [26,27]) effects on bone, glucocorticoids); prolonged immobilization or limited physical activity; malnutrition, most notably vitamin deficiencies and insufficient calcium intake [21], and secondary hormonal deficiencies (GH deficiency [17,19] and hypogonadism [5,23]). Importantly, lower bone mass was associated with worse quality of life in children treated for brain tumors [20,22].…”
Section: Introductionmentioning
confidence: 99%